Development of Integrated Thematic Electronic Worksheets With RADEC Learning Model Using Nearpod - Vianes Muliza Putri; Risda Amini (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research was motivated by that LKPD in schools is still in the form of handouts that are printed by teachers and distributed to students. The purpose of this research is to produce E-LKPD products using the RADEC-based Nearpod application. This type of research is development research with the ADDIE development model. Research instruments in the form of interviews, questionnaires, tests, and documentation. The research results obtained were Integrated thematic E-LKPD assisted by the RADEC-based Nearpod application in the elementary school stated in the very valid category. In the practicality questionnaire for the teacher's response score and the score for the student's practicality questionnaire in the very practical category. On the effectiveness used the N-Gain score percent test  with the effective category. So, it can be concluded that the developed ELKPD has fulfilled the categories of valid, practical, and effective to improve student learning outcomes.